2010
DOI: 10.1093/gbe/evq002
|View full text |Cite
|
Sign up to set email alerts
|

Both Noncoding and Protein-Coding RNAs Contribute to Gene Expression Evolution in the Primate Brain

Abstract: Despite striking differences in cognition and behavior between humans and our closest primate relatives, several studies have found little evidence for adaptive change in protein-coding regions of genes expressed primarily in the brain. Instead, changes in gene expression may underlie many cognitive and behavioral differences. Here, we used digital gene expression: tag profiling (here called Tag-Seq, also called DGE:tag profiling) to assess changes in global transcript abundance in the frontal cortex of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
90
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 80 publications
(168 reference statements)
12
90
0
Order By: Relevance
“…Consistent with this, previous studies have identified a large number of genes differentially expressed among primates [7][8][9][10][11][12][13][14][15][16], and in a few cases, have also found that the inter-species changes in gene expression level might explain differences in complex phenotypes between primates [17][18][19][20][21][22]. However, we still know little about the underling regulatory mechanisms leading to the differences in gene expression levels across species.…”
Section: Introductionsupporting
confidence: 54%
“…Consistent with this, previous studies have identified a large number of genes differentially expressed among primates [7][8][9][10][11][12][13][14][15][16], and in a few cases, have also found that the inter-species changes in gene expression level might explain differences in complex phenotypes between primates [17][18][19][20][21][22]. However, we still know little about the underling regulatory mechanisms leading to the differences in gene expression levels across species.…”
Section: Introductionsupporting
confidence: 54%
“…(b) Evidence for changes in energy transport In brain tissues, there is a consistent pattern of changes in expression of genes critical to aerobic energy metabolism [67,69,71,91]. This includes categories such as oxidative phosphorylation, electron transport and other nuclearencoded genes that function in the mitochondria.…”
Section: Evidence From the Evolution Of Gene Expression Between Humanmentioning
confidence: 99%
“…corticocortical connectivity | human transcriptome | association cortex | supragranular | brain evolution P atterns of gene expression in the cerebral cortex are generally conserved across species, reflecting strong constraints in the development and evolution of cortical architecture (1)(2)(3)(4)(5)(6). Previous work examining transcriptional variation in nonhuman primates and rodents indicate that molecular similarities between cortical regions in the adult brain are best explained by spatial proximity (7,8).…”
mentioning
confidence: 99%